EFEKTIVITAS IMPLEMENTASI KURIKULUM MERDEKA DALAM PENGEMBANGAN LITERASI FUNGSIONAL MELALUI PEMBELAJARAN TEKS PERSUASIF - Sari, Irma Resti Yulfita; Yudistira, Fauzian; Noviani, Dina Rahmah; Salsabila, Muzakki Robani; Jaja (CV. Adiba Aisha Amira, 2024)
Functional literacy is very useful in everyday life. Numeracy skills function effectively in learning, working and interacting throughout life. The development of functional literacy skills is very important because this ability refers to a person's capacity to engage in all activities that require literacy skills so that their groups and communities can function effectively and also to enable them to continue using their reading, writing and numeracy skills for themselves and public. In implementing functional literacy development, these skills can be seen in learning persuasive texts which play a significant role in developing functional literacy skills. Persuasive texts help students learn to construct arguments, develop critical and analytical thinking skills, and improve their ability to write and understand complex texts. This research aims to determine the effectiveness of the implementation of the independent curriculum in developing functional literacy through persuasive texts. This study used descriptive qualitative method. The data for this research are the results of interviews with teachers and students at the Cirebon City Tourism Vocational School. Data collection techniques use recording and note-taking techniques. The research results show that the Merdeka Curriculum is effective in developing students' functional literacy skills. From this research it was also found that discovery learning and project-based learning methods were said to be more effective for developing functional literacy of Cirebon City Tourism Vocational School students in the field of Office Management Automation.